Applying a motivational stage-based approach in order to study a temporary free public transport intervention. (September 2019) - Friman, Margareta; Maier, Raphaela; Olsson, Lars E.
Abstract: The present study examines temporary free public transport as an intervention for increasing public transport use, hence promoting sustainable mobility. The aims of the study are twofold: (1) to understand how psychological mechanisms relate to motivational stage-based models of behavioral change, and the role of such a model when implementing temporary free public transport, and (2) to determine the effectiveness of temporary free public transport on car-use behavior, public transport satisfaction and attitudes. A literature review of studies reporting temporary free public transport interventions was first carried out, resulting in 13 studies that yielded non-conclusive results. We then conducted an intervention and follow-up surveys of 190 participants who tested public transport for free for one month in the County of Värmland (Sweden). The results show that psychological mechanisms are crucial determinants of motivational stage-based models, whereby personal norms, attitudes and perceived behavioral control form the stage of change, and that social norms have an indirect effect through personal norms. Although an increased use of public transport was observed, only minor reduction in car use occurred. It was also found that participants moved up their motivational ladders, indicating a stronger motivation to reduce their car use post-intervention, something that may lead to a change in behavior over time. It is concluded that, although weak effects were observed on behavior in the short-term perspective, a temporary free public transport intervention may not be a waste of money, nevertheless, in a long-term perspective. Highlights: Norms, attitudes and perceived behavioral control are crucial factors in motivational stage-based models. Temporary free PT intervention leads to change in the motivational stage. Although limited behavior change was observed, a stronger motivation to change will be positive in the long-term. Positive effects on attitude towards public transport and travel satisfaction. Effects may be stronger when matching intervention to motivational stages of change.